Whole plant open chamber to measure gas exchange on herbaceous plant - Ferrari, Florencia (2016)
Much of our understanding about CO2 and H2O gas exchange in plants has been gained from studies at leaf level. Extrapolation of results to whole plant is difficult and not always accurate. In order to overcome this limitation, a chamber was designed to measure gas exchange at the whole plant level. The chamber developed in this work consisted on an acrylic cylinder 0.70 m high and 0.60 m wide. An incorporated blower was used to circulate air through the chamber and plant canopy from the bottom inlet upwards to the outlet tube providing a maximum flow of 0.072 m3 s-1. Air CO2 and water concentration were monitored with an infrared gas analyzer and temperature gradients were measured periodically with sensors. Air flow rates inside the chamber were 0.007, 0.012, 0.022, 0.047, and 0.072 m3 s-1. A comparative study showed that 0.022 or 0.047 m3 s-1 air flow rates did not modify substantially the natural environment within the chamber; measurements are close to real and exterior ones; temperature increased below 4 °C; photosynthetically active radiation (PAR) was reduced by 5%; and photosynthesis and evapotranspiration showed mean values with nonsignificant variations (22 ± 3.8 μmol CO2 m-2 s-1, and 15 ± 4.0 mmol H2O m-2 s-1, respectively). This chamber could be a useful tool to measure gas exchange of whole plants in herbaceous species under conditions of high evapotranspiration and for extended periods of time.